Local Wisdom as an Effort to Increase Immunity with Tawadhu Berwudhu to Prevent the Covid 19 Pandemic in Talang Village, Serdang Bedagai Regency - Syarifah Syarifah; Nelvitia Purba; Mukidi Mukidi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The Covid-19 pandemic that has plagued since 2020 has changed the behavior of the world community and is no exception in Indonesia including in this Tualang village by carrying out health protocons by increasing its role and vigilance in anticipating the transmission of the Covid 19 virus in the community of Tualang Village in public places and facilities so as to help minimize the impact. caused by Covid 19. can be developed by each party in accordance with regional characteristics by familiarizing and routine Berwudhuk is an alternative in preventing this virus. The method used is a research and development method in English called Research and Development. Is Research And Development. This research begins with the potential and problems in the New Order period to reduce the risk of transmission of covid 19 in Tualang Village. The analysis carried out in this study using the Analysis is descriptive qualitative. This research will focus on improving the product by testing it to experts and practical to get the conclusions from the results of this research. The results of the study can be argued that: the emergence of Covid 19 in early 2020 causes serious problems, not a few of this virus causes death. done to prevent this deadly virus. For Muslims every time they carry out prayers are required to perform ablution. Regular ablution or at least the fardu prayer five times and the midnight and duha circumcision prayers which have been used as guidelines in the life of the people of Tualang Village are the Law As Tool of Social Engineering means that people must act in accordance with what is required by the norms so that people must comply and apply these norms to prevent Covid-19. The activity of washing hands and other members is a minimum of seven times. However, if Muslims are able to maintain wudh uknya is believed to be able to help prevent this covid -19 virus. Therefore, for the Talang community, Tawadhu in carrying out routine ablution-related activities is a condition of every human being to submit to Allah SWT with sincere intentions wholeheartedly to avoid the Covid -19 pandemic.